Analisis Pedagogical Content Knowledge (PCK) Mahasiswa PG-PAUD dalam Mengajarkan Konsep Bilangan pada Anak Usia Dini - Ahmad Afandi; Pascalian Hadi Pradana (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study presents a comprehensive analysis of the Pedagogical Content Knowledge (PCK) profiles of 26 pre-service early childhood teachers regarding the teaching of number sense. The research is motivated by the urgency of mastering early mathematical literacy as a child's cognitive foundation, which is often hindered by teachers' limited pedagogical competence in transforming abstract content into concrete learning. Using a qualitative case study design, data were collected through Content Representation (CoRe) instruments, Pedagogical and Professional-experience Repertoires (PaP-eRs), analysis of Daily Lesson Plans (RPPH), and microteaching observations. The analysis assessed the mastery of Subject Matter Knowledge (SMK), covering Gelman and Gallistel’s counting principles (one-to-one correspondence, stable order, cardinality, abstraction, and order irrelevance), as well as PCK components including Knowledge of Content and Students (KCS) and Knowledge of Content and Teaching (KCT). The results revealed significant PCK profiles: 38.5% at the Pre-PCK level, 50% at the Growing PCK level, and only 11.5% reaching Maturing PCK. Key findings indicate that although the pre-service teachers possess adequate procedural knowledge regarding number sequences, there is a profound conceptual deficit in cardinality and one-to-one correspondence. Consequently, they tend to design drill-oriented, worksheet-based learning activities. Furthermore, the KCS ability to anticipate children's misconceptions was identified as the weakest aspect, as the prospective teachers often failed to detect subtle counting errors in children.